(untitled) (BAITUL HIKMAH, 2025)
This study aims to analyze the transformation of child guardianship law in Indonesian Muslim diaspora families by examining the relationship between positive legal norms, socio-religious practices, and maqāṣid al-syarī’ah approach. Using socio-legal methods, data were collected through document studies, semi-structured interviews, and observations of diaspora communities in the Europe, Middle East, and Asia Pacific regions. The results show that the problem of child custody in diaspora families is generally triggered by cross-jurisdictional divorce, mixed marriage, and parental absence, which has implications for the uncertainty of administrative rights and the certainty of the status of the child’s guardian. The settlement of guardianship is pursued through three main channels, namely the local state court, community religious institutions, and Indonesian legal administration. However, the disharmony between the three systems often creates a gap in legal protection for children. The maqāṣid al-shari’ah approach offers a transformative solution by emphasizing the comprehensive protection of children’s rights, both legally and socially. The conclusion of this study emphasizes the need for harmonization of cross-border guardianship mechanisms to ensure the fulfillment of the rights of diaspora children in a sustainable manner.